Understanding the Flygstad (Fløgstad) Figurine: Gaming Pieces, Kings, Gender and Fertility Rites. - Pentz, Peter (Medieval Archaeology, 2025)
The article examines a small, bearded figurine made from walrus tusk, discovered in 1796 in a burial mound at Flygstad, Norway, and discusses its potential role as a gaming piece, specifically a king from the board game hnefatafl. It explores a controversial group of similar early-medieval and Viking-Age figurines that depict men stroking or pulling their beards, suggesting that this gesture is closely linked to themes of masculinity, kingship, and fertility. The article posits that these figurines may symbolize not only gaming pieces but also reflect deeper cultural meanings related to male identity and social status in Viking society.